Incidence of peri-operative cardio-respiratory complications in smokers versus non-smokers - Ranjit, S; Bhattarai, B (Journal of Institute of Medicine Nepal, 2011)
Introduction: Smoking is considered to be an independent risk factor for many diseases as well as cardio-respiratory events in patients undergoing anaesthesia and surgery. This study was aimed at finding out the incidence of peri-operative cardio-respiratory complications in cigarette smokers undergoing intermediate and major surgery under general anesthesia with endotracheal intubation and compare with that in non smokers in our hospital.Methods: A prospective case control and single blinded study was conducted. Standard anaesthetic technique was employed to 40 current smokers who smoked 5 or more cigarettes per day for at least 5 years and 40 non smokers. Any adverse cardio respiratory adverse events like tachycardia during intubation, increased oral secretions, desaturation, bronchospasm, laryngospasm, severe coughingor pulmonary edema were recorded in each group. Chi-square test and Fischer exact test have been used to test the significance of events.Results: Increase in heart rate during intubation was significantly higher in smokers p